PREPARE-ing South Dakota Farm and Ranch Women for Advance Care Planning - Theresa Garren-Grubbs; MariJo Letizia; Mary Minton (Rural Nurse Organization; Binghamton University, 2020)
Purpose: Evaluate the impact of an advance care planning (ACP) educational session utilizing PREPARE for Your Care for South Dakota farm and ranch women and its ability to increase engagement in ACP and documentation of medical wishes in the form of an advance directive. Sample: A convenience sample of women (n = 23) represented members of the farm and ranch community in South Dakota who were participating in the Power of Women as AgVocates Conference. Inclusion criteria for this study included being 18 years old or older, female, and conference participation. Exclusion criteria included men and those under the age of 18. Method: This was a cross-sectional investigation, consisting of three phases, and included comparisons of the same sample population before and after an ACP intervention at different time intervals (baseline, 1 week after the educational session and 3 months after the educational session). Increased engagement in ACP was evaluated using a pre-test, post-test design and utilized the 15-item Advance Care Planning Engagement Survey. Demographic information including age and highest level of education completed was collected. Findings: In total, 23 women participated in education session. The median age range was 35-44 years of age. There were statistically significant increases in self-efficacy and readiness to complete ACP reported by participants. The objectives of this education session were met. Per the participants, this was an effective format for ACP. Advance directive completion rates did not increase. Conclusions: The use of PREPARE for Your Care during an education session on ACP can increase self-efficacy and readiness to engage in ACP. The format of this program is appropriate for future use in community settings with the farm and ranch population. Keywords: Advance Care Planning, farm and ranch women DOI: http://doi.org/10.14574/ojrnhc.v20i2.632